Analisis Efektivitas Biaya (Cost Effectiveness Analysis) Monoterapi Pada Pasien Preeklampsia Di Rsud Sleman - Yuni Andriani; Lutfi Hidiyaningtyas; Nendhi Wahyunia Utami (MEDIA ILMU KESEHATAN, 2023)
Background: Preeclampsia treatment if not treated immediately will cause seizures and even cause death. Rational treatment can be seen from the (outcome) therapy and costs. Pharmacoeconomic analysis can be used to see which drug is most effective in terms of therapeutic outcomes and the costs incurred to obtain that therapy.Objective: This study aims to analyze the cost-effective antihypertensive monotherapy in preeclampsia patients.Methods: The research was conducted at the Sleman Regional Hospital on inpatient preeclampsia patients for the 2021-2022 period. Retrospective data collection in the form of medical record data and financial administration. The effectiveness of therapy is calculated based on blood pressure and length of stay with ICER (Incremental Cost-Effectiveness Ratio) calculations.Results: The description of the characteristics of preeclampsia patients at Sleman Regional Hospital is dominated by those aged 20-35 years, 23 patients (51%), without comorbidities, 39 patients (87%). The most widely used antihypertensive monotherapy was Nifedipine in 33 patients (73%). The cost effective monotherapy is Nifedipine, with an ICER value of Rp. 3,258 based on blood pressure and an ICER of -Rp. 6,041 based on LOSConclusion: Monotherapy that cost effective for hospitalized preeclampsia patients at Sleman Regional Hospital is Nifedipine.